Role of mTOR Signaling in Female Reproduction - Guo, Zaixin; Yu, Qi (Frontiers in Endocrinology, 2019)
Mammalian target of rapamycin (mTOR) is a conserved serine/threonine kinase of the phosphatidylinositol kinase-related kinase family that regulates cell growth, metabolism and autophagy. Extensive research has linked mTOR to several human diseases including cancer, neurodegenerative disorders, and aging. In this review, recent publications regarding the mechanisms underlying the role of mTOR in female reproduction under physiological and pathological conditions are summarized. Moreover, we assess whether strategies to improve or suppress mTOR expression could have therapeutic potential for reproductive diseases like premature ovarian failure, polycystic ovarian syndrome, and endometriosis.